Simvastatin-loaded liposomal nanoparticles as treatment for adenomyosis in a patient-derived xenograft mouse model: a pilot study - Rachel Michel; Kathleen L. Vincent; Gregory W. Kirschen; Massoud Motamedi; Jamal Saada; Jinping Yang; Bulent Ozpolat; Gokhan S. Kilic; Mostafa A. Borahay (Journal of Obstetrics and Gynaecology)
Background Adenomyosis is a common gynaecological condition where ectopic endometrial glands and stroma grow within the myometrium. This condition has a high clinical burden impacting those afflicted with debilitating symptoms including heavy painful periods. Simvastatin is an oral hydroxymethylglutaryl-coenzyme A (HMG-CoA) reductase inhibitor, typically used to treat hyperlipidaemia. Simvastatin has recently shown promise for treating gynaecological conditions such as endometriosis and uterine fibroids with nanoliposomal formulations demonstrating improved efficacy. In this pilot study, we tested simvastatin-loaded liposomal nanoparticles on xenografted adenomyosis tissues in a patient-derived mouse model.Methods We surgically inserted oestrogen/progesterone pellets into mice, followed by adenomyosis tissue xenografts 15 days later. Mice were then randomised into three groups: control, simvastatin, and simvastatin-loaded liposomal nanoparticles (simvastatin-NP). We quantified the changes in adenomyosis xenograft size weekly using a calliper as well as ultrasound imaging 28 days after treatment, prior to sacrifice. We also measured the proliferation of biomarker Ki67 in the xenografted tissues using immunohistochemistry after animal sacrifice.Results Treatment with simvastatin-NP significantly reduced volume and weight of adenomyosis xenografts while attenuating Ki67 expression when compared to the control and simvastatin groups. Conclusions: This pilot study demonstrates promising improved efficacy of simvastatin delivered via liposomal nanoparticles. However, larger studies are needed to fully explore the potential of simvastatin-NP in adenomyosis.